التنظيم الدستوري والقانوني لحق مخاطبة السلطات العامة: دراسة مقارنة - يونس مها بهجت; جبار جمال ناصر (Journal of Legal Sciences, 2017)
The right to address public authorities by petitions and complaints is one of the individual means to participate in public affairs of individuals, because of what they (petitions) included of the important issues to the individual, society and public authorities alike, also the right to address public authorities gives the citizen a positive and important role in public life because it allows him to contact the authorities directly and submit his proposals and grievances, and the right to address public authorities is a real guarantor of rights and public freedoms and to protect them from abuse by any party in order to achieve more stability in the community and enhances the spirit of citizenship and affiliation among its individuals.